Student satisfaction with the heutagogical approach in education - IRENE GUMIRAN (Universidade Estadual de Alagoas, 2024)
The heutagogical approach places a strong emphasis on learner autonomy and the enhancement of their potential for a self-directed learning, technology utilization also can make it easier to integrate heutagogy in the classroom, improving learning results and increasing learner engagement. Thus, the student satisfaction is an essential element of higher education that can support student achievement. This study aims to describe the satisfaction of Political Science students with the heutagogy approach in education at the Universidad de Manila, Philippines using a descriptive quantitative approach with a survey method. The subjects of this study were the twenty-nine (29) students of the Political Science education program at Universidad de Manila, Philippines who are currently enrolled in Qualitative and Quantitative Analysis of Political Data (PSC222). The sampling used was purposeful which is a non-probability. The result reveals that the students were very satisfied (62.1%) with the quality of teaching, satisfied (58.6%) with the course content, satisfied (37.9%) with the campus facilities, and very satisfied (55.2%) with the student support and services. The results disclosed that student satisfaction is a vital aspect in higher education as it affects their motivation and academic success, especially in this era of Globalization, Technology, Information and Communication Technology (ICT), is increasing, which forces the world of education to have positive innovations for the advancement of education.